A pilot study of dimeticone oils versus sodium carbonate treatment for tungiasis: A randomized cohort trial in Homa Bay County, Kenya. - Kana Suzuki; Yasuhiko Kamiya; Chris Smith; Satoshi Kaneko; Gordon Okomo; Asiko Ongaya; Evans Amukoye (PLoS Neglected Tropical Diseases)
Background Tungiasis is a cutaneous parasitosis caused by the female flea Tunga penetrans. Two-component dimeticone (NYDA) is the only treatment for tungiasis recommended by the World Health Organization; however, this topical drug is not available in Kenya. In Western Kenya, sodium carbonate is commonly used in the treatment of tungiasis. This study evaluated the 7-day cure rates for tungiasis by comparing sodium carbonate and NYDA treatments in Homa Bay County, Kenya. Methodology/principal findings This was a randomized, observer-blinded, parallel-treatment cohort trial. Twenty-three eligible children with 126 flea infections were matched and randomized. All participants received both treatments, with one treatment on each foot. We recorded all health conditions/information, including inflammation scores and adverse events. Observations were performed on days 3, 5, and 7 using a digital microscope to confirm dead or live fleas based on the viability signs. Twenty-three children aged 3-13 years were analyzed. The proportion of dead fleas on day 7 was higher after NYDA treatment than after 5% sodium carbonate treatment (87% versus 64%, respectively, P = 0.01) NYDA. Median survival was 5 days for both treatments; NYDA had significantly higher trend of flea non-viability rate than 5% sodium carbonate (P<0.01). There were no significant differences in the inflammation score or pain/itchiness between the two treatments. On the last day, 14 children indicated their preference for NYDA in future treatment of tungiasis, whereas nine children preferred the 5% sodium carbonate solution. Conclusions/significance NYDA was significantly more effective than 5% sodium carbonate for tungiasis treatment. Both treatments were safe but the children preferred NYDA more. Future studies with more participants and an extended observation period are warranted to confirm our findings. The findings suggest that NYDA should be made more available in tungiasis endemic area. Trial registration UMIN-CTR; UMIN 000044320.